The Relationship between Dividends Policy and Firm Value, Profitability, Liquidity and Leverage Evidence from Saudi Stock Exchange (Journal of Namibian Studies : History Politics Culture, 2023)
The study sought to discover the effects resulting from the dividend policy on the firm's value, profitability, liquidity and leverage, which were interpreted in the light of the signaling hypothesis. In an emerging market such as the Saudi Stock Exchange, information related to dividends helps current and potential investors to make decisions about investment opportunities available in the market, and dividends are an important tool used by firms to attract investments.